Analyzing the significance of art and architecture in Dan Brown's novels and its impact on readers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Art and architecture play vital roles in Dan Brown's novels, serving as both plot devices and vehicles for exploring deeper themes. Their significance lies not only in their aesthetic appeal but also in the historical, symbolic, and sometimes mystical dimensions they embody. The impact of art and architecture on readers in Brown's novels is multifaceted, evoking intrigue, prompting reflection, and enriching the storytelling experience.